Robust task space trajectory tracking control of robotic manipulators - Galicki, Mirosław (Zielona Góra: Uniwersytet Zielonogórski)
This work deals with the problem of the accurate task space trajectory tracking subject to finite-time convergence. Kinematic and dynamic equations of a redundant manipulator are assumed to be uncertain. Moreover, globally unbounded disturbances are allowed to act on the manipulator when tracking the trajectory by the end-effector. Furthermore, the movement is to be accomplished in such a way as to reduce both the manipulator torques and their oscillations thus eliminating the potential robot vibrations.
Keywords: redundant manipulator; task space trajectory cracking; finite-time control; Lyapunov stability; vibration reduction